Keberfungsian Keluarga dan Prioritas Menikah pada Dewasa Transisi: Studi Komparasi Berdasarkan Pekerjaan Ibu - Kusumawardhani, Sri Juwita; Deviana Annisa Salsabila; Ghiandra Putri Regawa; Hermeilia Megawati (Jurnal Psikologi Jambi, 2025)
This study investigates marriage priorities and perceptions of family functioning among emerging adults. The study will compare two groups of emerging adults based on their mother’s employment status: emerging adults with stay-at-home mothers and working mothers. The research participants were 332 respondents obtained using the convenience sampling technique, with the criteria emerging adult (18-29 years old), unmarried, married parents, and living on Java Island. The instruments used were the Marital Horizon Questionnaire and McMaster Family Assessment Device Subscales GF12. The data analysis technique used to test the hypotheses in this study is the Kruskal-Wallis Test. The research results show that there are no differences in marriage priority (p = .445, p>0.05) and family functioning (p = .964, p>0.05) between Emerging Adulthood with stay-at-home mothers and Working Mothers. The mean score for family function in the group of emerging adults with working mothers (166.72) and the group of emerging adults with stay-at-home mothers (166.28). Meanwhile, the mean score for marriage priority in the group of emerging adults with working mothers (162.48) and the group of emerging adults with stay-at-home mothers (170.52). This study concludes that emerging adults raised by working mothers still maintain a positive perception of family functioning and consider marriage a priority.